Pemanfaatan Gas Metana Sebagai Sumber Energi di TPA Winongo Kota Madiun - Era Dinisiadela Dhalia; Raden Kokoh Haryo Putro (Jurnal Serambi Engineering, 2024)
The problem of waste, which is getting worse almost every year, is an aspect of special interest in several countries in the world, including Indonesia. The increasing population in a country is the most instrumental aspect in increasing the volume of waste as well as the need for final processing sites or known as (TPA) in the urban area. Winongo Landfill, located in Manguharjo District, Madiun City, is the site to be studied. In Winongo Landfill Madiun City, a controlled landfill is used with a waste system that is filled with soil after the waste looks full, causing more methane gas. This research was conducted by using and calculating the amount of methane gas produced based on the composition and amount of waste expected to enter the Winongo landfill in 2024. The methane gas produced from organic waste ranges from 13,574.812 kg CH4 to 15,190.861 kg CH4. It is therefore necessary to make the best use of energy sources from the methane gas produced so that it benefits the surrounding community and does not pollute the environment.